Creating the productive workplace : places to work creatively - Clements-Croome, Derek (New York ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2018)
The built environment affects our physical, mental and social well-being. Here renowned professionals from practice and academia explore the evidence from basic research as well as case studies to test this belief. They show that many elements in the built environment contribute to establishing a milieu which helps people to be healthier and have the energy to concentrate while being free to be creative. The health and well-being agenda pervades society in many different ways but we spend much of our lives in buildings, so they have an important role to play within this total picture. This demands us to embrace change and think beyond the conventional wisdom while retaining our respect for it. Creating the Productive Workplace shows how we need to balance the needs of people and the ever-increasing enabling technologies but also to take advantage of the healing powers of Nature and let them be part of environmental design. This book aims to lead to more human-centred ways of designing the built environment with deeper meaning and achieve healthier and more creative, as well as more productive places to work.
Part I: Health, well-being and productivity landscape --
1. Effects of the built environment on health and well-being / Derek Clements-Croome --
2. The business case for sustainable healthy buildings: health, productivity and economic consequences / Derek Clements-Croome --
3. The multi-sensory experience in buildings / Briony Turner, Derek Clements-Croome and Kay Pallaris --
4. Pleasure and joy, and their role in human life / Michael Cabanac --
5. User-centered workspace design: applications of environmental psychology to space for work / Jacqueline C. Vischer --
6. Change makers: rethinking the productive workplace through an art design lens / Jeremy Myerson --
Part II: Research evidence --
7. Lessons from schools for productive office environments: the SIN model / Peter Barrett --
8. Effects of indoor air quality on decision-making / Usha Satish, Piers MacNaughton and Joseph Allen --
9. Workplace productivity: fatigue and satisfaction / Shin-ichi Tanabe and Naoe Nishihara --
10. Proving the productivity benefits of well-designed offices / Nigel Oseland --
11. Optimising well-being and productivity through an ergonomics-based approach / Stephen Bowden --
12. Lighting for productive workplaces / Jennifer A. Veitch --
13. The Robert L. Preger Intellegent Workplace: the living laboratory at Carnegie Mellon University / Volker Hartkopf, Vivian Loftness, Azizan Aziz, Khee Poh Lam, Steve Lee, Erica Cochran and Bertrand Lasternas --
14. Thermal and IAQ effects on school and office work / Pawel Wargocki and David P. Wyon --
15. Measuring the IEQ contribution to productivity and well-being: the importance of the built environment indoor environment quality on economic productivity and the contributing factors which lead to improved performance / Vyt Garnys, Travis Hale and Adam Garnys --
Part III: Experiential evidence from surveys and building case studies --
16. A visual language of the workplace: new planning principles for modularized work / Peter A. Bacevice, Hannah Beveridge and Liz Burow --
17. The people-building interface: it's a two-way street / Judith Heerwagen, Kevin Kampschroer, Bryan C. Steverson and Brian Gilligan --
18. Workplace: a tool for investment / Kevin Reader --
19. Productivity in buildings: the killer variables: twenty years on / Adrian Leaman and Bill Bordass --
20. Enjoy work: a case study on Chiswick Park / Jason Margrave, Ron German and Kay Chaston --
21. The need for a wellness integrator to ensure healthy buildings and businesses / Victoria Lockhart, Mallory Taub and Ann Marie Aguilar --
22. Achieving holistic sustainability: considering wellness alongside resource use in buildings / Jenn McArthur --
23. Making the economic case for good design of workplaces / Sarah Daly --
24. Building performance: the value management approach / Bernard Williams --
Part IV: Future horizons --
25. Stranger than we can imagine: the future of work and place in the twenty-first century / Mark Eltringham --
26. How to prevent today's ergonomic office problems in the future? / Veerle Hermans --
27. Future landscapes / Despina Katsikakis --
28. Coda / Derek Clements-Croome.
"First edition published by E & FN Spon 2000. Second edition published by Taylor & Francis 2006."
Includes bibliographical references and index.
ARC
Trim Education
Keywords: Industrial productivity -- Congresses; Environmental protection -- Congresses; Environmental policy -- Congresses; Work environment -- Congresses; Architecture